Characterization of p-groups with a maximal irredundant 10-covering / Rawdah Adawiyah Tarmizi and Hajar Sulaiman - Tarmizi, Rawdah Adawiyah; Sulaiman, Hajar (2015)
A group G is covered by a collection of its proper subgroups if it is equal to the union of the collection. A covering is called irredundant if there is no proper sub-collection is also a covering of G. A covering in which all members are maximal subgroups of G is called maximal.